Impact of price limits on SGX Nikkei 225 futures. - Tan, Wee Chuan. (2008)
This paper investigates the impact of price limits, as a control mechanism, on volatility and liquidity for the SGX Nikkei 225 futures. Time-stamped bid and ask tick data from January 1, 1990 to December 31, 2001 are employed to investigate the impact on volatility and liquidity. Market liquidity is studied by examining the minute-by-minute trading volume and intraday bid-ask spreads (BAS).